Pengelolaan Ekonomi Rumah Tangga Berbasi “ILM’ Tadbir Al Manzil ” Bagi Wirausaha Perempuan - Naelati Tubastuvi; Ika Yustina Rahmawati; Sulistiyani Budiningsih (Prisani Cendekia, 2022)
The purpose of Science and Technology for the Community is expected that members of the Aisyiyah Banyumas Regional Leadership will be able to become agents of change for women or housewives around them, by applying the concept of household economic management based on Ilm' Tadbir Al Manzil. From these insights, it is expected to be able to provide benefits and contributions to the management of family finances / assets so that assets are divided into short-, medium and long-term needs, especially to learn to invest, besides that savings measures can also be done by being disciplined in budget priorities to avoid debt bondage